The The Effect of Active Gambir (Uncaria gambir) Fraction on TNF-α Protein Expression and Lesion Size in White Rats Gastritis Model - Ni Wayan Lisa Suasti; Lunsi Oktafitria; Ellya Aidia; Rahmad Dhani (HM Publisher, 2018)
Background: Gambir (Uncaria gambir) is empirically used to treat abdominal pain and vomittus caused by gastritis because of its anti-inflammatory effects, especially flavonoid. This study aims to determine the effect of active gambir fraction on TNF-α protein expression and wound size in white rats gastritis model. Methods: The research method used experimental study design in vivo with post test with control group design. Rats were divided randomly in 11 groups and were induced to be gastritis for 1 day. Group 1 (negative control) was given aquadest of 5 mL, group 2 (positive control) was administered ranitidine 10 mg/kgBW, groups 3, 4, and 5 were given n-hexane fraction, groups 6, 7 and 8 were given a water fraction, and groups of 9, 10, and 11 were given ethyl fractions with each group receives dose of 20, 40, and 80 mg/kgBW and all groups were treated for 3 days. Rats were dissected on 5th day for examination of gastric mucosal lesion size and performed ELISA expression of TNF-α expression of gastric mucosal tissue. The results of this study were assayed by SPSS 18. Results: The result of the research using Kruskal-Wallis test showed that there were significant differences (p <0.05) of the lesions size between the sample groups where control positive, ethyl fraction 20, 40, 80 mg/kgBW, and water fraction 20, 40 mg/kgBB had the gastric mucosal lesion size differed significantly with the negative control group, while the TNF-α protein expression test using Kruskal-Wallis showed that there was a significant difference (p <0.05) TNF-α levels of all groups against the negative control. Conclusion: Active gambir fraction had a potention to reduce size of mucose gaster lesion and reduce expression of TNF-α protein.